The effect of background clutter on visual search in video conferencing - Yelda Semizer; Ruth Rosenholtz (Cognitive Research)
Abstract The use of video conferencing tools has become increasingly common recently. The visual displays in these tools are highly complex, being composed of multiple faces with varying image quality and lighting conditions. On top of this, users have the ability to choose their own backgrounds. Some choose simple artificial backgrounds, some appear in front of a real or simulated room, and some use something more abstract. How do these choices affect the user’s ability to use the tool, for example, finding the current speaker or a reaction symbol? Vision science can certainly provide answers to these questions; however, most search studies use simple displays with a uniform background, or more recently, real-world scenes. How does what we know about search generalize to these more complex displays? The current study sought to examine how our understanding of visual search applies to well-controlled video conferencing displays. Specifically, we investigated the effect of display clutter (i.e., background complexity and variability) on perceptual tasks relevant for video conferencing. In an eye-tracking set-up, participants searched either for the speaker whose image was highlighted (Experiment 1) or for a reaction symbol (raised-hand) embedded on one of the attendees’ background. Results showed a significant effect of background complexity and variability, suggesting that search performance declined as the display clutter increased. Image-based analysis showed that the choice of backgrounds mediated these effects, suggesting that some virtual backgrounds were not optimal for perceptual processes.